Food insecurity and subjective cognitive complaints among adults aged ≥ 65 years from low- and middle-income countries. - Smith, Lee; López Sánchez, Guillermo F.; Shin, Jae Il; Kostev, Karel; Underwood, Benjamin R.; Oh, Hans; Soysal, Pinar; Veronese, Nicola; Schuch, Felipe; Tully, Mark A.; Koyanagi, Ai (European Journal of Nutrition, 2023)
Purpose: To date, no study has investigated the association between food insecurity and subjective cognitive complaints (SCC). Thus, the aims of the present study were to examine this association among older adults in low- and middle-income countries (LMICs), and to identify the potential mediators in this association, given the importance of SCC in dementia risk among older people, and the projected particularly large increase in dementia in this setting. Methods: Cross-sectional, community-based, nationally representative data from the World Health Organization (WHO) Study on global AGEing and Adult Health (SAGE) collected between 2007 and 2010 were analyzed. Two questions on subjective memory and learning complaints in the past 30 days were used to create a SCC scale ranging from 0 (No SCC) to 100 (worse SCC). Past 12 month food insecurity was assessed with two questions on frequency of eating less and hunger due to lack of food. Multivariable linear regression and mediation (Karlson–Holm–Breen method) analyses were conducted to assess associations. Results: Data on 14,585 individuals aged ≥ 65 years [mean (SD) age 72.6 (11.5) years; 55.0% females] were analyzed. Severe food insecurity (vs. no food insecurity) was associated with 9.16 (95% CI = 6.95–11.37) points higher mean SCC score. Sleep/energy (mediated% 37.9%; P < 0.001), perceived stress (37.2%; P = 0.001), and depression (13.7%; P = 0.008) partially explained the association between severe food insecurity and SCC. Conclusion: Food insecurity was associated with SCC among older adults in LMICs. Future studies should assess whether addressing food insecurity among older adults in LMICs can improve cognitive health.